2007
DOI: 10.1103/physreve.76.021913
|View full text |Cite
|
Sign up to set email alerts
|

Role of molecular tilt in thermal fluctuations of lipid membranes

Abstract: Long-wavelength thermal fluctuations of lipid membranes are adequately described by the Helfrich elastic model. On the other hand, fluctuations of wavelengths comparable with bilayer thickness exhibit significant deviations from the prediction of the elastic model and are typically assumed to be dominated by microscopic surface tension due to protrusion of lipid molecules into the solvent. We present evidence that the short-wavelength modes of a lipid membrane are dominated by fluctuations of the tilt of lipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
102
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(110 citation statements)
references
References 20 publications
8
102
0
Order By: Relevance
“…However, additional structural properties of the lipid bilayer, such as lipid tilt [72][73][74][75][76][77][78], may have a more substantial effect on bilayer-mediated protein interactions. Moreover, integral membrane proteins may tilt to reduce hydrophobic mismatch, as suggested by Monte Carlo and molecular dynamics simulations [119,120].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, additional structural properties of the lipid bilayer, such as lipid tilt [72][73][74][75][76][77][78], may have a more substantial effect on bilayer-mediated protein interactions. Moreover, integral membrane proteins may tilt to reduce hydrophobic mismatch, as suggested by Monte Carlo and molecular dynamics simulations [119,120].…”
Section: Discussionmentioning
confidence: 99%
“…(3) and the corresponding "zeroth-order" models [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68] capturing curvature-and fluctuation-mediated protein interactions absorb the molecular details of lipids and membrane proteins into effective material parameters. To provide a more detailed description of bilayer-protein interactions, a number of extensions and refinements of these models have been developed [44,45,[69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86]. For instance, the effect of bilayer-protein interactions on the elastic properties of lipid bilayers can be captured [44,81,82,86] by allowing for spatial variations in the values of the elastic bilayer parameters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…22 The effects of the molecular tilt have also been introduced. 28,29 These studies claim that the phospholipid tilt may be more relevant than the protrusions. Using this approach it was shown that the simulation data can be very well fitted, even for membrane lateral lengths of a few nanometers.…”
Section: Introductionmentioning
confidence: 99%